Clinical and Pathogenetic Aspects of the Course of Peptic Ulcer Disease with Concomitant Duodenal Stasis - Ya. M. Vakhrushev; M. S. Busygina (SINAPS LLC, 2020)
Objective: to assess the characteristics of the course of peptic ulcer in combination with duodenostasis (DS) according to clinical, electrophysiological, and morphological studies.Materials and methods. The study included 169 patients with duodenal ulcer, of which two groups were formed: the observation group consisted of 107 patients with duodenostasis-associated duodenostasis, the comparison group included 62 patients with duodenal ulcer without concomitant duodenostasis-associated duodenostasis. The control group consisted of 30 practically healthy individuals who did not have complaints from the gastrointestinal tract. The results of clinical, objective studies, and laboratory and instrumental data were used in the verification of YB and duodenostasis-associated duodenostasis. To study the closing function of the gatekeeper, the ratio of intraduodenal pressure to intrahastral pressure was used. To study the acid-forming function of the stomach was used device "Gastroscan-5M", engine - gastroenterological GEM-01 "Gastroscan-GEM" ("Istok-System", Fryazino). The mucus-forming function was studied using a Sialo Test (research and production center (RPC) "Eco-Service", Saint Petersburg).Results. In patients with ulcer with concomitant DS, the duration of ulcerative history was longer - 10,2 ± 1.2 years than in patients with ulcer without concomitant DS - 9,6 ± 1.3 years (p = 0,041). Complications were revealed in 33 (30.8%) patients with ulcer with concomitant DS, in 4 (6,4%) patients with ulcer without concomitant DS (χ 2 = 20,9, p = 0,017). Patients in the observation group were more likely to have erosive-ulcerative lesions of the mucosa than in the comparison group (86 (81,2%) and 23 (37,8%) patients, respectively (χ 2 = 33,4, p <0,001). pressure to intragastric in patients of the observation group was significantly reduced in relation to the control group (p = 0,001). In case of YAB with duodenal ulcer with DS according to Gastroscan-HEM, the Pi / Ps coefficient (stomach) postprandially increased by 3,5 times compared with the control In patients of the observation group, the overall level of sialic acids significantly prevailed over firs in the control group (p <0,001) and the comparison group (p <0,001).Conclusion. Concomitant duodenostasis, acting on the main etiopathogenetic links of ulcerogenesis, aggravates the course of peptic ulcer disease, increases the frequency of its complications.